Massive Arteriovenous Malformation of Tongue: A Case Report - Koneru, Dr. Anila; M, Dr. Vanishree; Mastammanavar, Dr. Deepa; Katapadi, Dr. Vidyachandra; Manvikar, Dr. Vardendra; Latha, Dr. H Aparna (International Journal of Innovative Research in Medical Science, 2025)
“Vascular malformation” is a general term used to define a group of lesions, present at birth, shaped by an anomaly of angiovascular or lymphovascular structures. In this paper, we present a case of arteriovenous malformation involving the left dorsum of tongue of a 25-year-old female followed by a review of the literature. A 25-year-old Female patient complains of a large swelling on the left upper and lower surface of tongue since 3 years and increased in size over the last 4 months. On intraoral examination, a large reddish purple-colored lesion - the anterior portion of the tongue. The overlying skin appeared nodular. On palpation, the swelling was soft, fluctuant and compressible. Lesion blanched with pressure- Diascopy, and pulsations were felt at the posterior end. Provisional diagnosis of Vascular Malformation was given with a differential diagnosis of Hemangioma. MRI revealed Hyperintense T2-weighted images showed vessels with flow voids confirms a fast flow vessel. These findings were related to Arteriovenous Malformation. Histopathological examination revealed the presence of large and small vessels lined by endothelial cells. These vessels are filled with blood and supported by fibrous connective tissue stroma. A Final Diagnosis of AV Malformation of Tongue was given. To conclude, clinical diagnosis with proper mode of investigations such as MRI, CT, Doppler and Angiography helps in rapid diagnosis and avoiding morbidity related to the vascular lesions.